Pilah Pilih Sampah, Strategi Pemberdayaan Komunitas Ibu Rumah Tangga Dusun Kebonbawang - Sri Hartini; Margaretha Novian Cahyani; Dewi Kurnianingsih Arum Kusumahastuti (CV. ITTC INDONESIA, 2025)
The surge in organic waste in Kebonbawang Hamlet, particularly from households, is triggering an environmental crisis. Empowering housewives through independent composting is a sustainable solution to reduce waste volume and increase environmental awareness. This program aims to foster awareness and active participation of housewives in household waste management. Training in waste separation techniques, compost production, and waste reduction strategies is conducted through workshops and intensive training. The methods used include outreach, practical training, and composting mentorship. Housewives are involved in every stage, from waste sorting, compost material preparation, to monitoring results. The results show a significant increase in understanding and skills in organic waste management. The resulting compost has been successfully used to fertilize agricultural land around the hamlet. Empowering housewives in independent composting has successfully reduced organic waste volume and provided economic and environmental benefits for the Kebonbawang community. This program has the potential to be replicated in other areas with similar problems.